PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN DI KELAS: JENIS IMPLEMENTASI DAN DAMPAK BAGI SISWA - Herdianto Wahyu Pratomo; Aqilatun Ni'mah; Qoni'ah Al Munasiroh; Imroatus Sulthoniyah; Dita Arisona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of multicultural education in schools and its impact on students. The research employs a narrative literature review method by examining various studies, policies, and educational practices in different contexts. The findings reveal that multicultural education is implemented through curriculum integration, experience-based teaching strategies, and inclusive school policies. These implementations positively impact students by enhancing their understanding of cultural diversity, fostering inclusivity and tolerance, and developing social skills. However, challenges such as inadequate teacher training, limited resources, and gaps between policy and practice remain. Therefore, this study recommends strengthening teachers' capacity in multicultural education, providing more inclusive learning materials, and implementing systematic school policies to support diversity